Green Supports for Heterogeneous Photocatalysts and their Application in Wastewater Remediation - Thattil, Preeja. P.; Jeyaleela, G. Dayana; Kavitha, K.; Selvanayagi, K. P.; Sumathi, S. (Chemistry and Biochemistry: Research Progress Vol. 2, 2025)
An overview of water pollution, its causes and the current scenario of water scarcity at global and national levels is addressed in the introductory section. The need for advanced oxidation techniques such as the use of homogeneous and heterogeneous photocatalysts is briefly presented. In this new era, researchers look into the development of green and eco-friendly photocatalysts such as metal oxide/graphene quantum dots and carbon-based supported photocatalysts. Supported photocatalysts such as carbon dots, activated carbon, biodegradable polymers, clay and glass plates or glass beads immobilized photocatalysts are also thoroughly reviewed and well presented. A highlight on the patented technologies for wastewater treatment is also presented for the benefit of the readers which might encourage more research contributions to the field.